The long memory dynamics of the market quotations of selected Stock Companies and Warsaw Stock Index - Łuczyński, Wiesław (Economics and Business Review, 2007)
The analysis of the results obtained allows to establish the short memory of the stationary time series deprived of the stochastic trend, the permanent memory of the non stationary data of the Hodrick-Prescott trend and the declining memory of the non stationary time series of the quotation dynamics of the stock companies. As results from the research, the spectral analysis of the stock quotations does not reveal the fluctuations in the business conditions. The fluctuations with the period of about 34, 20 and 14 sessions with the quotations of particular companies and WIG correspond to the periods 8-10, 5-6 and 3-4 weeks. (original abstract)